Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00185 tex.type: [object Object]
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking